Pengaruh Penerapan Sistem E-Filling Terhadap Kepatuhan Pelaporan SPT Tahunan Tenaga Kependidikan Orang Pribadi di Universitas Islam Indonesia - Khairunnisa, Inas; Mukhsin, Muhamad; Matalatta, Andy (Disclosure: Journal of Accounting and Finance, 2022)
This study aims to determine the effect of implementing the e-filling system on individual taxpayer compliance at the Islamic University of Indonesia. This study uses primary data by distributing questionnaires to Universitas Islam Indonesia (UII) education staff employees who have a TIN and have used e-filling. The research sample is 78 individual taxpayers. The results showed that the implementation of the e-filing system had a significant effect on taxpayer compliance. This study suggests to the Directorate General of Taxes to simplify the e-filing system because many taxpayers find it difficult to use the system and are expected to further socialize the procedures for using e-filing